Two-dimensional ferroelectric metal CuCrX2 (X = S, Se) for efficient electrocatalysis - Ying Wang; Chengliang Lu; Menghao Wu (Computational Materials Today)
Electrocatalysts play an important role in the oxygen reduction and evolution reactions (ORR/OER) in fuel cells. Although ferroelectric polarizations may favor catalysis in some cases, ferroelectrics are supposed to be insulators while electrocatalysts should be metallic to facilitate rapid electron transfer. We note that robust vertical ferroelectricity in 2D metallic CuCrX2 (X = S, Se) has been experimentally confirmed in recent reports. In this paper we show first-principles evidence that they can be ideal candidates as noble-metal-free OER/ORR bifunctional catalysts with low overpotentials, high conductivity and active site density, which are long-sought but remain elusive. The catalysis is remarkably facilitated by their ferroelectric polarizations, which can be revealed by charge analysis and the large difference in overpotential between two surfaces, and the estimated minimum ORR overpotential (0.28 V) and OER overpotential (0.43 V) of few-layer CuCrX2 are all much lower compared with prevalent electrocatalysts based on noble metal.